Perspective of geriatric patients on advance care planning in Denmark: a qualitative study - Maurice A Lembeck; Hanne Pedersen; Ellen Astrid Holm; Emilie Ramberg; Kirstine Dahmke; Elisabeth Nielsen-Hannerup; Ida Søndergaard Madsen; Sofie Rerup (BMJ Open)
Objective Most previous studies on advance care planning (ACP) have focused on patients with specific diseases and only a few on frail ageing individuals. We therefore decided to examine the perspective of geriatric patients on ACP. Our research questions include if, when, with whom and with which content geriatric patients wish to have ACP conversations.Design Participants were interviewed either in the hospital or in their own home. The interviewer followed a semistructured interview guide. Interviews were transcribed and analysed using the systemic text condensation method.Setting Geriatric department in a regional hospital in a rural area in Region Zealand, Denmark.Participants We included 11 geriatric patients aged above 65 who had been referred for geriatric inpatient or outpatient assessment. Participants were clinically judged by experienced geriatricians to have sufficient physical and mental capacity to take part in an interview.Results This study’s main finding is that geriatric patients have varying preferences and feelings towards ACP. Some expressed concerns about ACP, especially regarding personal fear to talk about end-of-life (EOL) decisions, and whether a busy healthcare system has the resources to conduct ACP. Proper timing of ACP seemed unrelated to specific age but related to perception of health situation. The health professional involved should be well trained and a person the participant could trust. Most participants wanted family members to participate. Concerning content, participants mentioned quality of life, fear of losing their spouse, earlier experience with death, and practical concerns regarding funeral and will.Conclusion Among geriatric patients, feelings towards ACP are mixed. Even participants who were generally positive towards the concept uttered concerns about the circumstances when talking about EOL topics. Health professionals therefore should approach ACP discussions with caution. Further studies aiming to develop guidelines describing the proper way to introduce and perform ACP in this patient group are needed.